O homicídio da escravizada Luíza: um estudo de caso sobre as relações de poder e sociabilidade no Recife oitocentista. - Mesquita, Joyce Conceição de (2022)
The present report is the result of a case study, specifically, that of the enslaved Luiza, murdered by her master in December 1863. Through the analysis of qualitative information about what happened, consulted through the more than two hundred pages that constitute the criminal process belonging to the Memorial da Justiça de Pernambuco, but also through the contemporary press and other archival sources, we produced as a result of the research a History in Comics (HQ). In this comic, in addition to the interrupted life of Luíza, motto and route at the same time, we discuss the working conditions of the enslaved - especially female slave labor in the urban environment -, the spaces of sociability, the relations of power and gender in Recife do Brasil. beginning of the second half of the 19th century. This didacticpedagogical instrument is aimed at high school students, aiming at stimulating new knowledge not subordinated to teaching-learning methods based on memorization.